Tutoring to build teacher candidates' competence as reading teachers. Issue 3 (27th May 2022) - Nickel, Jodi; Chadwick, Joy
ABSTRACT: As part of a literacy development course and a subsequent language arts methods course, teacher candidates (TCs) participated in a twenty-week community service learning partnership tutoring elementary students in reading. Through TCs' case study course assignments, survey data, and a focus group interview, the researchers analyzed TCs' growth including understanding of reading concepts, responsive teaching, and teaching values. The study provides specific evidence for the value of the tutoring experiences for the preparation of reading teachers including building their knowledge, responsiveness, reflective capacity, and awareness of issues in literacy instruction.